Global review of tobacco product flavour policies. Issue 4 (15th May 2020) - Erinoso, Olufemi; Clegg Smith, Katherine; Iacobelli, Michael; Saraf, Sejal; Welding, Kevin; Cohen, Joanna E
Abstract : Objective: We determined which countries prohibit flavoured tobacco products and the details of those restrictions in order to identify possible gaps and opportunities for these and other countries to address. Methods: We reviewed the grey literature, scanned news articles and consulted with key informants and identified 11 countries and the European Union (EU) that ban or restrict tobacco product flavours. We reviewed policy documents for their stated policy rationale, terms and definitions of flavours, tobacco products covered and restrictions on the use of flavour imagery and terms on tobacco product packaging. Results: Countries with a tobacco product flavour policy include the USA, Canada, Brazil, Ethiopia, Uganda, Senegal, Niger, Mauritania, EU (28 Member States), Moldova, Turkey and Singapore. Most of the countries' policies provide a rationale of dissuading youth from taking up tobacco use. Ten of the 12 policies use the terms 'flavours' (n=6) or 'characterising flavours' (n=4). Six policies cover all products made entirely or partly of tobacco leaf. Countries consistently prohibit flavours associated with fruits, vanilla and spices. The USA and Niger make an exception for menthol, while Mauritania and Uganda do not specify the scope of flavours or ingredients covered by their policies. Eight policies make no specific reference to restricting flavour descriptors on tobacco product packaging. Conclusion: Countries looking to implement policies restricting flavours in tobacco products can build on existing comprehensive policies. Future research could examine the implementation and impacts of these policies, to inform other countries interested in acting in this policy domain.